Spiritualitas Fransiskan dalam Konteks Kerja Modern:Membangun Kualitas Pelayanan Berkelanjutan - Wuriningsih, FR; FR Wuriningsih; Setyaningtyas, Nerita; Sinurat, Agnes Uliarta; Krishna W, Cornelius (Perigel: Jurnal Penyuluhan Masyarakat Indonesia, 2025)
Community service currently focuses on the implementation of Franciscan spiritual values ​​in the context of modern work for employees of the Saint Joseph Gedangan Semarang Convent. This program aims to answer the challenges of integrating spiritual values ​​with the demands of professionalism in household services in the monastery environment. Based on the situation analysis, five main problems were identified: (1) the gap between spiritual values ​​and work practices; (2) work saturation and decreased motivation; (3) differences in work approaches between generations of employees; (4) obstacles to coordination between service units; and (5) a suboptimal employee development system. This program is designed with a participatory-reflective approach through four stages: preparation, Franciscan spirituality understanding workshops, workplace mentoring, and evaluation. The methods used combine andragogical and spiritual-integrative approaches. The solutions offered include value integration workshops, motivation revitalization programs, appropriate technology training, cross-generational dialogue, collaborative team formation, and employee development plan preparation. The expected outcomes are improved service quality, strengthening of Franciscan value-based work culture, and ongoing professional and spiritual development for 16 employees serving a community of 28 nuns with diverse needs. The sustainability of the program is ensured through long-term mentoring and the formation of a core group that will continue the implementation of Franciscan spiritual values ​​in the context of daily work.